`y' = d/(d(theta))cot^2(sin(theta))`

`= 2 cot (sin(theta)) * d/(d(theta)) [cot(sin(theta))]`

`= 2cot(sin(theta))*(-csc^2(sin(theta)))*d/(d(theta)) (sin(theta))`

`= 2 cot(sin(theta))*(-csc^2(sin(theta)))*cos(theta)`

`= -2 cos(theta)*cot(sin(theta))*csc^2(sin(theta))`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now